The influence of the fatigue process zone size on fatigue life estimations performed on aluminum wires containing geometric discontinuities using the Theory of Critical Distances. (October 2018) - Adriano, V.S.R.; Martínez, J.M.G.; Ferreira, J.L.A.; Araújo, J.A.; da Silva, C.R.M.
Highlights: Fatigue life predictions were performed in wires with geometric discontinuities. S-N curves were produced to calibrate and to validate the numerical methodology. A new approach to evaluate the equivalent stress in the Volume Method is proposed. The effect of the fatigue process zone size in the life predictions is evaluated. Abstract: The aim of this work is to predict fatigue life of aluminum alloy wires 6201-T81 containing geometric discontinuities using the Theory of Critical Distances (TCD). These wires were taken from a 900 MCM All Aluminum Alloy Conductor (AAAC 900 MCM) used in overhead power transmission lines. The equivalent stress was evaluated by means of the Point Method (PM) and the Volume Method (VM), based on the maximum principal stress ( σ 1 ). Regarding the latter method, a new approach to evaluate the equivalent stress inside a material volume defined by the shape of a sphere is presented. The relation between the critical distance and the number of cycles to failure was calibrated using two distinct methodologies: the first one uses two S-N curves, one curve of a plain wire and the other of a notched wire; the second methodology also uses two S-N curves, however, in this case, both curves refer to wires containing different geometric discontinuities. Therefore, S-N curves of wires containing artificial geometric discontinuities like holes and notches were produced, both to calibrate the critical distance relation and to validate the life predictions. When the life estimations were performed based on the first calibration, the results were considered not satisfactory. However, when the second calibration was used, almost all the predictions were inserted within scatter bands regarding the experimental data used to calibrate the model. The authors believe that the difference in accuracy between predictions obtained by the two calibration methods could be related to a statistical size effect associated to the fatigue process zone size.